1998
DOI: 10.1073/pnas.95.15.8692
|View full text |Cite
|
Sign up to set email alerts
|

Targeted disruption of Pax1 defines its null phenotype and proves haploinsufficiency

Abstract: The murine paired box-containing gene Pax1 is required for normal development of the vertebral column, the sternum, and the scapula. Previous studies have shown that three natural Pax1 mouse mutants, the undulated alleles, exhibit phenotypes of different severity in these skeletal elements. Nevertheless, these analyses have not clarified whether the semidominant Undulated short-tail (Un s ) mutation, in which the complete Pax1 locus is deleted, represents a null allele. Moreover, the analyses of the classical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
110
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(119 citation statements)
references
References 27 publications
9
110
0
Order By: Relevance
“…T-gene-mutant heterozygous mice exhibit short tails, and the homozygous mutant mice are embryonic lethal (Wilson and Conlon, 2002). Another example is the Pax1 knockout mice, in which an apparent kinked tail is observed only in the Pax1 null homozygotes (Wilm et al, 1998). It is possible that the observed tail abnormality was induced by the insertion of the LYL1 transgene into the genomic loci of a certain crucial gene.…”
Section: Discussionmentioning
confidence: 99%
“…T-gene-mutant heterozygous mice exhibit short tails, and the homozygous mutant mice are embryonic lethal (Wilson and Conlon, 2002). Another example is the Pax1 knockout mice, in which an apparent kinked tail is observed only in the Pax1 null homozygotes (Wilm et al, 1998). It is possible that the observed tail abnormality was induced by the insertion of the LYL1 transgene into the genomic loci of a certain crucial gene.…”
Section: Discussionmentioning
confidence: 99%
“…Several transcription factors have been shown to play essential roles in sclerotome development like Bapx1. Pax1 is one of the transcription factors required for the axial skeleton development (Wilm et al 1998). The vertebral defects of Pax1 mutants showed remarkable similarities to those of Bapx1.…”
Section: Discussionmentioning
confidence: 99%
“…Pax1 expression is initially detected in the ventromedial part of newly segmented somites, giving rise to the sclerotome, and is con®ned to the anlagen of the intervertebral discs onwards. Pax1 mutants suffered from severely disturbed formation of both the vertebral bodies and intervertebral discs, like Bapx1 mutants (Wallin et al 1994;Wilm et al 1998). Pax9, another member of the Pax gene family, is highly homologous to Pax1, and is expressed in developing sclerotome in a overlapping pattern to that of Pax1 (Neubu Èser et al 1995).…”
Section: Molecular Mechanisms Underlying the Vertebral Defects Observmentioning
confidence: 99%
“…These results from classical mutants suggested that Pax1 may be haploinsufficient, and would lead to perinatal lethality in the homozygous state. Indeed, targeted mutation of Pax1 proves haploinsufficiency for some, but not all sclerotomal derivatives that express Pax1 (Wilm et al, 1998). This could be due to the ectopic activation of Nkx2.2 in the absence of Pax1 (Kokubu et al, 2003), or alternatively, another gene may functionally compensate for the loss of Pax1 in unaffected sclerotome.…”
Section: C Transcription Factors Of the Pax Genementioning
confidence: 99%